Failure of condition - Wilmot-Smith, F; Frederick John Wilmot-Smith (2013)
This thesis is an investigation of a doctrine generally known as ‘failure of consideration’, but which I term ‘failure of condition’. I have two principal aims. First, to clarify quite what the doctrine of failure of condition is. Secondly, to explain why it has the effects it does – in particular, why it justifies the response of restitution. The doctrine, at core, concerns conditional transfers: when a transfer is made conditionally, and the condition fails, the transfer can be recovered. For this reason, I term the doctrine ‘failure of condition.’ I investigate the nature of this relationship and argue that the reason why the transfer is conditional is that the agent’s intention to make the transfer was itself conditional. The justification of restitution is a more complex affair than is customarily accepted – but there is a valid justification lurking not far from the surface of orthodoxy. A secondary concern of the thesis is to re-examine an old theory in the field of common mistake, frustration and termination following a breach of contract. It used to be thought that these doctrines could be explained by failure of condition. That theory has fallen out of favour – it seems that no one accepts it today. This rejection rests upon a confusion over the nature of the doctrine of failure of condition. Once the nature of this doctrine has been clarified, we can see how closely the various doctrines align with one another; we can also see where the true difficulty with the failure of condition explanation lies.